The Effect of Split Nitrogen Application on the Transport of Residue-Derived Carbon in Different Carbon Pools in Black Soil - Xianni Chen; Shanglong Zhang; Shaofei Jin; Jiakai Gao; Siyu Dong; Minggang Xu; Xugang Wang; Dayong Guo; Xiaofeng Xu (Agronomy)
To discriminate the transport characteristics of residue-derived carbon (Cres) from soil native carbon (Csoil) in black soil with split nitrogen application, a 540-day incubation study was conducted with four treatments: Control (unamended soil), R (soil + residue), RN1 (soil + residue + one-time application of nitrogen fertilizer), and RN3 (soil + residue + three-time application of nitrogen fertilizer). The total soil organic carbon (TOC) of the incubated soil was separated into three fractions: light fraction (LF), occluded-particulate organic matter fraction (OPOM), and heavy fraction (HF). The results showed that the TOC content was significantly higher in the RN1 and RN3 (averaging 20.77 g/kg) than in the R (18.43 g/kg) and Control (19.03 g/kg) after 540 days. Nitrogen fertilization significantly increased the residual rate of HF−Cres by 11.75% (p < 0.05), and the RN3 treatment significantly increased the residual rate of OPOM−Cres by 18.84% (p < 0.05) and reduced the loss rate of LF−Csoil by 77.01% (p < 0.05) compared with the R treatment. The soil catalase activity declined continuously along with incubation and was higher in the RN3 treatment than in the RN1 treatment after 180 days. The correlation analysis showed that the LF−Csoil and −Cres, as well as the HF−Csoil and catalase activity, were the main contributors to the TOC. Conclusively, nitrogen application, especially split nitrogen application, could stimulate the ability of soil to retain exogenous carbon and preserve native carbon.